(untitled) (SAARC Journal of Agriculture, 2023)
Dry direct seeding (DDS) is a water saving rice cultivation technology. The sowing of dry direct seeded rice in boro season is generally delayed when grown under the T. aman rice – Rabi crops – DDS boro rice pattern. An experiment was conducted at the Agronomy Field of Bangladesh Agricultural University, Mymensingh to study the effect of sowing date and irrigation schedule on growth and yield of DDS boro rice. The experiment used two sets of treatments (a) two sowing dates viz. 22 February and 13 March; and (b) six irrigation regimes viz. no irrigation, one irrigation at 25% Field Capacity (FC), two irrigations at 25% FC and 1 week after (WA) 25% FC, three irrigations at 25% FC, 1WA 25% FC and 2 WA 25% FC, four irrigations at 25% FC, 1 WA 25% FC, 2 WA 25% FC and 3 WA 25% FC and one irrigation at 3 weeks after 25% FC and the treatments were arranged in a split-plot design with three replications allocating sowing dates into the main plot and irrigation schedule into the subplots. BRRI dhan58 was used as test crop. The result showed that grain yield of the crop did not differ significantly for sowing on 13 March and 22 February. The study revealed that BRRI dhan58 sown on 13 March with four irrigations applied at 25% FC, 1 WA 25% FC, 2 WA 25% FC and 3 WA 25% FC produced the highest economic return and hence it is concluded that the sowing date of boro rice could be delayed up to 13 March with four irrigations. SAARC J. Agric., 21(2): 67-80 (2023)